(untitled) (Bangladesh Journal of Public Administration, 2019)
The purpose of the study is to assess the effectiveness of the project, “Market Development Initiative for Bondhu Chula”. Most people in the rural area of Bangladesh use a traditional cooking device. Biomass is the primary source of energy for cooking devices. The limitations of traditional cooking devices demand the introduction of Bandhu Chula, which is claimed to be energy efficient and environment-friendly. Hence potential entrepreneurs were trained to produce and sell this new device. The study employed a qualitative approach. Fourteen stakeholders were interviewed. The study found that users were not aware of this, and the local government representatives were not sensitized. Only 4 per cent of households at Kachuai union of Patiya upazila of Chottogram were found to use Bondhu chula – a fact, which indicates that the project failed to create entrepreneurs. However, the users, and women, in particular, were found to be happy to use this cooking device as it is less time consuming, energy-efficient, less costly and easy to cook.